Clinical features, investigation and treatment of post-traumatic syringomyelia. - Shannon, N (1981)
Thirteen patients who sustained spinal cord trauma causing persisting disability, developed new symptoms, the chief one of which was severe pain unrelieved by analgesics. The clinical diagnosis of post traumatic syringomyelia was confirmed in each case by means of myelography, as well as endomyelography in seven patients. In every case exploration of the spinal cord syrinx was performed. Ten patients were troubled by severe pain while three patients were mainly subject to altered sensation in the upper limbs. Of the six patients who had initially sustained complete cord transections, three were treated by cord transection and three were treated by syringostomy. The seven patients who sustained incomplete cord lesions were all treated by syringostomy. The patients who initially sustained incomplete sensory motor spinal cord damage had a better symptomatic response to surgery than hose who had sustained a complete spinal cord lesion. The ten patients whose main symptom was severe pain were completely relieved of their symptoms by surgery.